Kajian Terkini CoronaVirus Disease 2019 (COVID-19) - Chicy Widya Morfi; Ahmad Junaidi; Elsesmita Elsesmita; Diana Nur Asrini; Dya Mulya Lestari; Irvan Medison; Russilawati Russilawati; Fauzar Fauzar; Roza Kurniati; Finny Fitry Yani (Fakultas Kedokteran, Universitas Andalas, 2020)
The COVID-19 outbreak in Wuhan, Hubei Province, China, caused by a newly known coronavirus strain, SARS-CoV-2, up to March 3th, 2020, has caused 90.870 confirmed cases to be reported from 72 countries (including Indonesia) with 3.112 deaths (CFR 3,4%). Upper airway swab and lower airway aspirate specimens from suspected patients are required for examination by the RT-PCR microbiological method for establishing COVID-19. There are no specific antivirals for the management of COVID-19. On January, 30th, 2020 WHO has established Covid-19 as the Public Health Emergency of International Concern (PHEIC), but the increase in the number of cases is fast enough so that on March,11th 2020, WHO has established Covid-19 as a pandemic.